2018
DOI: 10.1186/s12974-018-1166-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 2-AG hydrolysis differentially regulates blood brain barrier permeability after injury

Abstract: BackgroundAcute neurological insults caused by infection, systemic inflammation, ischemia, or traumatic injury are often associated with breakdown of the blood-brain barrier (BBB) followed by infiltration of peripheral immune cells, cytotoxic proteins, and water. BBB breakdown and extravasation of these peripheral components into the brain parenchyma result in inflammation, oxidative stress, edema, excitotoxicity, and neurodegeneration. These downstream consequences of BBB dysfunction can drive pathophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 53 publications
1
25
2
Order By: Relevance
“…In light of previous studies showing that CB1 agonists improve survival and outcome in TBI patients and reduce neuroinflammation and neuronal excitotoxicity in rodent TBI models 25 , 71 73 , the observed lasting loss of endocannabinoids discloses an underlying mechanism, and supports the idea that inhibition of FAAH, the enzyme catalyzing the breakdown of AEA, OEA and PEA, could be a novel therapeutic approach. In rodent models, FAAH inhibitors attenuated TBI-evoked inflammatory markers in association with better performance in balance beam walking and Morris water maze 27 , 28 .…”
Section: Discussionsupporting
confidence: 78%
“…In light of previous studies showing that CB1 agonists improve survival and outcome in TBI patients and reduce neuroinflammation and neuronal excitotoxicity in rodent TBI models 25 , 71 73 , the observed lasting loss of endocannabinoids discloses an underlying mechanism, and supports the idea that inhibition of FAAH, the enzyme catalyzing the breakdown of AEA, OEA and PEA, could be a novel therapeutic approach. In rodent models, FAAH inhibitors attenuated TBI-evoked inflammatory markers in association with better performance in balance beam walking and Morris water maze 27 , 28 .…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, IL‐1β led to a discontinuous distribution of claudin‐5 along the plasma membrane of brain endothelial cells 75 . Apart from claudin‐5, LPS‐induced systemic inflammation was also associated with degradation of occludin 82 . Another recent study showed that peripheral cytokines reduced expression of ZO‐1 in mice with pre‐existing tumors 83 …”
Section: Mechanisms Of Peripheral Inflammation‐induced Bbb Disruptionmentioning
confidence: 99%
“…Inflammation drives the activation of the neurovasculature, thus disrupting the integrity of the BBB and substantially inducing its permeability as reported in several neurodegenerative diseases. Inhibition of MAGL activity, and, therefore, modulation of PGs expression were recently shown to prevent an inflammation-driven increase in BBB permeability [112] suggesting a dual role of the AA pathway controlling neuro-vascular coupling and BBB integrity/permeability. However, it should be stressed that changes to the BBB upon immune challenges are not restricted to intracellular transport but also affect paracellular transport and immune cell transmigration.…”
Section: Regulation Of Intracellular Transport Across the Bbb During mentioning
confidence: 99%